Synthesis of N-Aryl α-Ketoamides, α-Ketoesters, α-Ketothioesters and Their Applications in Quinoxalinone Preparation - Singh S.; Sureshbabu P.; Sabiah S.; Kandasamy J. (My University, 2025)
Synthesis of N-aryl α-ketoamides, α-ketoesters and α-ketothioesters were demonstrated from N-Ts and N-Boc α-ketoamides via transamidation and transesterification reactions. The reactions proceeded at room temperature in the presence of DBU and provided the desired products in good to excellent yields in a short time. A regioselective synthesis of biologically relevant quinoxalinones was achieved in good yields from N-aryl α-ketoamides via nitration followed by reduction reactions. © 2022 Wiley-VCH GmbH.